Program Studi Ilmu Kelautan, Fakultas Perikanan dan Ilmu Kelautan, Universitas Dipenogoro - Kharisma, Dian; Suryono, Chrisna Adhi; Nuraini, Ria Azizah Tri (Departemen Ilmu Kelautan, Fakultas PerikanJurusan Ilmu Kelautan, Universitas Diponegoro)
Human activities such as setlement, harbor, industry and fishing and bivalve catching in the shoreline directly or indirectly will force the changing of waters environment quality, for example the changing of physical and chemical quality of waters. Ecological study on benthic such as bivalve has an important rule because its high life tolerances could describe the environmental changing of the waters. In the dynamic environment, biology analysis, in particular biota benthic community analysis, could give clear description on waters area quality. This research intends to discover point of ecology bivalvia and also examined the correlation of waters quality towards bivalve ecological value. The research was held on March 3, March 24 and April 18, 2012 in 8 stations in Eastern Semarang waters. The material research was bivalve. The research indicates that 10 species from 5 families which are Anadara granosa, Anadara gubernaculum, Anadara inaequivalvis, Anadara pilula, Placuna placenta, Pharella javanica, Siliqua winteriana, Mactra violacea, Marcia hiantina and the highest affluence as 1274,4 Ind/HaÂ² ( station III), Paphia undulate. Average Diversity index (Hâ€™) of bivalve was around 0,3-1,2. Average Uniformity Index (e) was around 0,4-0,9. Bivalve distribution pattern in the research location in general indicated grouped distribution (Clumped). The result of cluster analysis divided 3 class areashile the lowest was found in class I. Double linier regression indicated examined waters parameter which were temperature, salinity, depth, organic content and silt depend on the affluence and diversity of bivalve.